Antioxidant activity and cell migration effect of standardized extract of centella asiatica for wound healing properties - Abdul Aziz, Huwaida; Bakhtiar, M. Taher; Sh. Ahmad, Afnan; Darnis, Deny Susanti (2015)
The present study demonstrates the antioxidant activity and cell migration effect of a standardized extract of C. asiatica. The ethanol extract was fractionated into seven fractions via vacuum liquid chromatography. The interest compound in the fractions was qualitatively identified using thin layer chromatography and the positive fraction with asiaticoside was further quantified using reverse-phase HPLC. The result showed that the methanol fraction of extract contains more than 10% of asiaticoside. The fraction also exhibited antioxidant activity with IC50 value of 463.8 µg/mL as DPPH (1,1-diphenyl-2-picrylhydrazyl) scavenger while IC50 value of 587.9 µg/mL in ABTS (2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)) radical scavenging capacities.The asiaticoside rich fraction was tested on mouse embryonic fibroblast NIH3T3 and human dermal keratinocyte HaCaT. Based on cell viability test of MTT (methylthiazol tetrazolium) colorimetric assay, both mouse embryonic fibroblast NIH3T3 and human dermal keratinocyte HaCaT showed significant stimulation against methanolic fraction of extract at the concentration of 100 µg/mL and 0.19 µg/mL. Besides, the extract showed almost no toxicity effect at concentrations tested since their IC50 could not be determined in concentration ranging from 100 µg/mL to 0.19 µg/mL. Due to all the concentration tested caused more than 80% cell viability, the concentrations chosen for the scratch assay is randomly chosen based on their concentration level of highest (100 µg/mL), medium (6 µg/mL), and lowest (0.2 µg/mL). In the scratch assay, only methanol fraction of extract with concentration 0.2 µg/mL showed significant cell migration effect on HaCaT compared to positive control (P < 0.05).